A Case of Epistaxis as the First Sign of Acute Idiopathic Thrombocytopenic Purpura. (8th February 2021) - Tajima, Shori; Matsumoto, Fumihiko; Anzai, Takashi; Hara, Satoshi; Suzuki, Yo; Ikeda, Katsuhisa
Abstract : Idiopathic thrombocytopenic purpura (ITP) is an acquired thrombocytopenia caused by the action of autoantibodies against platelet antigens. It is traditionally defined by a platelet count of less than 10 × 10 4 / μ L. Most patients with ITP are asymptomatic; however, symptoms have been confirmed in some cases. Conversely, it is very rare to find epistaxis as the first sign of ITP. We report the case of an 84-year-old man who came to the ear, nose, and throat department with severe and repeated epistaxis. We decided to keep him hospitalized as it was very difficult to stop the nasal bleeding. A full blood count showed a platelet level of only 1000/ μ L. Hematologic results confirmed the diagnosis of ITP. The patient underwent treatment with intravenous gamma-globulin, platelet transfusions, and romiplostim with a favorable response.